Cr-induced phase instability and hierarchical microstructure development in Co-based superalloys - Zaiser, Erika; Meng, Wenxing; Zhou, Xuyang; Mantha, Lakshmi; Pavel, Michael J.; Neumeier, Steffen; Long, Yan; Weaver, Mark L.; Gault, Baptiste; Wu, Yuan; Vogel, Florian (Journal of Materials Science & Technology, 2026)
Reproducibility of hierarchical γ/γ' microstructures in Co-based superalloys significantly influences their reliability and performance at elevated temperatures. This study investigates the formation and stability of such microstructures in nominally identical Co-9Al-9W-8Cr alloys. Despite nearly identical composition and heat treatment, significant microstructural differences emerged, including the formation of a hierarchical γ/γ' + γ architecture in one variant. Using scanning electron microscopy (SEM), atom probe tomography (APT), wavelength-dispersive spectroscopy (WDS), inductively coupled plasma optical emission spectroscopy (ICP-OES), and Thermo-Calc simulations, we identify subtle local Cr fluctuations and incomplete homogenization as key drivers of phase instability. High Cr levels alter partitioning behavior, promote the formation of the χ-Co3W phase, modify the γ matrix composition, reducing supersaturation and affecting γ particle formation inside γ' precipitates. APT analyses across multiple locations reveal significant nanoscale compositional variability, underlining the need for statistical sampling. Our findings show that hierarchical microstructures can form under narrow local conditions, with γ' size and local chemistry. The results highlight the sensitivity of the Co-Al-W-Cr system and the importance of precise process control to achieve reproducible, stable microstructures for advanced Co-based superalloys.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Atom probe tomography; Co-base superalloys; Hierarchical microstructure; Material characterization; Phase stability; γ/γ' microstructure